Clinical caring science as a scientific discipline. Issue 3 (14th November 2016) - Rehnsfeldt, Arne; Arman, Maria; Lindström, Unni Å.
Abstract : Background: Clinical caring science will be described from a theory of science perspective. Aim: The aim of this theoretical article to give a comprehensive overview of clinical caring science as a human science‐based discipline grounded in a theory of science argumentation. Findings: Clinical caring science seeks idiographic or specific variations of the ontology, concepts and theories, formulated by caring science. The rationale is the insight that the research questions do not change when they are addressed in different contexts. The academic subject contains a concept order with ethos concepts, core and basic concepts and practice concepts that unites systematic caring science with clinical caring science. In accordance with a hermeneutic tradition, the idea of the caring act is based on the degree to which the theory base is hermeneutically appropriated by the caregiver. The better the ethos, essential concepts and theories are understood, the better the caring act can be understood. In order to understand the concept order related to clinical caring science, an example is given from an ongoing project in a disaster context. Comprehensive reflection: The concept order is an appropriate way of making sense of the essence of clinical caring science. The idea of the concept order is that concepts on all levels need to be united with each other. A research project in clinical caring science can start anywhere on the concept order, either in ethos, core concepts, basic concepts, practice concepts or in concrete clinical phenomena, as long as no parts are locked out of the concept order as an entity. If, for example, research on patient participation as a phenomenon is not related to core and basic concepts, there is a risqué that the research becomes meaningless.